Colitis A Practical Approach to Colon and Ileum Biopsy Interpretation (Springer International Publishing, 2018)
This revised and updated second edition explains how to analyze endoscopic mucosal biopsies of the ileum and colon. As in the first edition, the diagnosis and follow up of colitis in general and inflammatory bowel diseases in particular is covered and this edition also includes new chapters on ileitis and optimal biopsy procedures. The basic lesions are described using multiple drawings together with an explanatory text and endoscopic and histological photographs. A review of various differential diagnostic issues and types of colitis is also included. Colitis: A Practical Approach to Colon and Ileum Biopsy Interpretation is aimed at general pathologists and pathologists in training and also gastroenterologists to help them understand how a precise diagnosis can be reached.